Sex-specific and pleiotropic effects underlying kidney function identified from GWAS meta-analysis - Sarah E. Graham (Nature Portfolio, 2019)
Estimated glomerular filtration rate (eGFR) is a measure of kidney function and used to characterize chronic kidney disease. Here, Graham et al. identify 53 novel loci for eGFR in a GWAS meta-analysis, a subset of which are associated with other common diseases, such as diabetes and hypertension, based on PheWAS.